Morphological, Physiological and Biochemical Characteristics of Indian Field Hockey Players of Selected Age Groups - Indranil Manna; Gulshan Lal Khanna; Prakash Chandra Dhara (Al Ameen Medical College, 2011)
Objectives: The morphological, physiological and biochemical variables at various stages of growth and development provide valuable information for selection of players of different age groups. Methods: One hundred and twenty (N= 120) field hockey players volunteered for this study. The players were divided equally (n=30) into 4 groups: (i) under 16 years (U16), (ii) under 19 years (U19), (iii) under 23 years (U23) and (iv) senior (SR). Selected morphological, physiological and biochemical variables were measured in the laboratory. Results: Results showed significantly higher (P<0.05) body mass, height and LBM in the U23 and senior players when compared to U16 and U19 players. However, significantly (P<0.05) lower percent body fat was noted in U16 and U19 players as compared to U23 and senior players [Body fat (%): (U16- 18.7 ± 2.0, U19-15.5 ± 1.4, U23-13.9 ± 1.2, SR-12.0 ± 0.5]. It was observed that in U19 players possess significantly higher (P<0.05) VO2max than the other age group players [VO2max (ml kg-1 min-1): U16- 54.6 ± 2.8, U19-57.0 ± 3.9, U23-56.0 ± 3.7, SR-54.1 ± 4.0]. Further, significantly higher (P<0.05) anaerobic power, strength, haemoglobin (Hb), serum urea and uric acid was noted in the U23 and senior players when compared to U16 and U19 players. The values of total cholesterol (TC), triglyceride (TG), high density lipoprotein cholesterol (HDL-C), and low density lipoprotein cholesterol (LDL-C) were significantly higher (P<0.05) in the upper age group (U23 and senior) players when compared to junior (U16 and U19) players. Conclusion: The unique profile of age related changes should be taken into consideration while selecting the players in teams.